Frequency of polycystic ovarian syndrome among patients presenting with acne - Jabeen, Sadia; Asad, Faria; Rani, Zahida; Khurshid, Khawar; Pal, Sabrina Suhail (Journal of Pakistan Association of Dermatologists, 2018)
Objective To determine the frequency of polycystic ovarian syndrome among patients presenting with acne. Â Methods 200 female patients having grade I-IV acne vulgaris, fulfilling inclusion and exclusion criteria were enrolled in the study after taking informed consent. They were screened for the presence of polycystic ovarian syndrome (PCOS) by using Rotterdam criteria 2003. Â Results Out of 200 females with acne vulgaris, 92 (46%) had polycystic ovarian syndrome. Age of the patients ranged from 14-40 years. In grade I to IV acne 6%, 16%, 12% and 12% patients had PCOS, respectively. Â Conclusion Polycystic ovarian syndrome is not uncommon in patients with acne vulgaris. However it is not related to the severity of acne. Â